(untitled) (Geographical Journal of Nepal, 2020)
Climate change will affect forest vegetation communities, and field surveys have already indicated measurable distribution range shifts in some tree species. As forests play an important role in stabilizing steep slopes and provide vital ecological goods and services, the Government of Nepal has been encouraging forest restoration and sustainable management. However, reforestation and afforestation programs should consider the long term survivorship of the trees selected for reforestation to build climate adaptation and resilience. Thus, the choice of species should include species that would be expected to grow within the elevation zone or in the particular habitat under future climate change scenarios. In this analysis, we have assessed the response of 12 important tree species to climate change using the IPCC A2A GHG scenario with GCM-based climate envelopes to provide guidelines and recommendations for climate change-integrated forest restoration and management in the Chitwan-Annapurna Landscape (CHAL). The results indicate that several species could exhibit range shifts due to climate change, with an overall trend for species in the lower elevations to move northwards or further up the slopes within the current area of distributions. Analyses such as this, though not perfect, can help to make critical and informed decisions to support long-term forest restoration programs.